The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-67302-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental representation and episodic-like memory of own actions in dogs

Abstract: We investigated whether dogs remember their spontaneous past actions relying on episodic-like memory. Dogs were trained to repeat a small set of actions upon request. then we tested them on their ability to repeat other actions produced by themselves, including actions performed spontaneously in everyday situations. Dogs repeated their own actions after delays ranging from a few seconds to 1 hour, with their performance showing a decay typical of episodic memory. The combined evidence of representing own actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…In addition, owners may have behaved with their dogs in slightly different ways during exposure while applying the protocol at home and this may have affected the dogs' ability to learn, but it is unlikely that such small differences would have resulted in the failure of learning even only two toy-names of all naïve dogs but one in the naïve group and success in learning multiple toy-names of all dogs in the other group. Furthermore, training protocols applied by the owners at home are typically successful 35,37,38 . Consistently with our results, Ramos and Mills 35 showed that typical dogs could successfully learn commands for actions but not for objects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, owners may have behaved with their dogs in slightly different ways during exposure while applying the protocol at home and this may have affected the dogs' ability to learn, but it is unlikely that such small differences would have resulted in the failure of learning even only two toy-names of all naïve dogs but one in the naïve group and success in learning multiple toy-names of all dogs in the other group. Furthermore, training protocols applied by the owners at home are typically successful 35,37,38 . Consistently with our results, Ramos and Mills 35 showed that typical dogs could successfully learn commands for actions but not for objects.…”
Section: Discussionmentioning
confidence: 99%
“…This work suggests that dogs' representation of their body size extends beyond the olfactory modality [8] and past actions [7]. Prior research on self-representation, using the mirror-mark test, has found mixed results with non-humans, some of which may be due to problems resulting from adapting primate-centric cognitive paradigms to nonprimates [8].…”
Section: Discussionmentioning
confidence: 81%
“…Research since the late 1990s has substantially broadened our understanding of the cognitive abilities of the domestic dog-in particular, how dogs perceive the world and interact with others. The greatest majority of research focuses on social cognitive abilities, such as gaze-and point-following [1,2] and use of others' attention [3,4]; other research Animals 2021, 11, 620 2 of 16 looks at the possible result of such social cognitive skill, such as perspective-taking [5,6] and representation of self [7]. Less well studied are the contributions of foundational perceptual abilities to cognition.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to answer unexpected questions has been shown in mammals such as dogs ( Fugazza et al, 2020 ), rats ( Crystal, 2013 ), and non-human primates ( Menzel, 1999 ). As an example, rats trained to get a reward differently depending on whether they recently experienced food or not, can be randomly asked this question throughout normal foraging and exploration.…”
Section: Behavioral Abilities That Emerged In Early Mammalsmentioning
confidence: 99%